Emotion Regulation Training Based on Cognitive Behavioral Therapy to Reduce Anxiety Levels in Adolescent - Afifah, Nursita; Boediman, Lia Mawarsari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Untreated anxiety may cause various problems in teenagers, such as difficulty in daily activities, social relationship problems, lack of academic performance, and other more complex problems. This research was a quasi-experimental research with a one-group pretest-posttest design that aims to examine the effect of emotion regulation training based on Cognitive Behavior Therapy (CBT) in reducing adolescent anxiety levels. The participants consisted of 5 female adolescents (13-14 years) who had moderate to severe anxiety and emotion dysregulation problems. Training is carried out in 5 sessions of 1-1.5 hours. Difficulties in Emotion Regulation Scale Short Form (DERS-SF) and Depression Anxiety Stress Scales (DASS 21) were used to measure the level of emotion dysregulation and anxiety before, after, and 3 weeks after the training. The results showed decreased emotion dysregulation (26.9%-30.5%) and anxiety (17.1%-42.8%) among participants. Emotion regulation training based on CBT was effective in increasing the ability to manage emotions and reducing anxiety levels in adolescents. This training can be considered as a group intervention method to overcome anxiety problems in adolescents. Masalah kecemasan yang tidak ditangani berpotensi menimbulkan berbagai hambatan pada remaja, seperti kesulitan melakukan aktivitas sehari-hari, masalah dalam relasi sosial, kurangnya performa akademik dan berbagai persoalan lain yang lebih kompleks. Penelitian ini merupakan penelitian kuasi eksperimen dengan one-group pretest-posttest design yang bertujuan menguji efektivitas pelatihan regulasi emosi berbasis Cognitive Behavior Therapy (CBT) dalam menurunkan tingkat kecemasan pada remaja. Partisipan penelitian ini adalah 5 orang remaja perempuan (13-14 tahun) yang memiliki masalah kecemasan dan disregulasi emosi tingkat sedang hingga berat. Pelatihan dilakukan dalam 5 sesi dengan durasi 1-1,5 jam pada tiap pertemuan. Pengukuran dilakukan dengan Difficulties in Emotion Regulation Scale Short Form (DERS-SF) dan Depression Anxiety Stress Scales (DASS 21) untuk mengetahui perubahan tingkat disregulasi emosi dan kecemasan sebelum, setelah dan 3 pekan setelah pelatihan dilaksanakan. Hasil penelitian menunjukkan adanya penurunan disregulasi emosi (26,9%-30,5%) dan kecemasan (17,1%-42,8%) pada partisipan. Pelatihan regulasi emosi berbasis CBT efektif meningkatkan kemampuan mengelola emosi dan menurunkan tingkat kecemasan pada remaja. Pelatihan ini dapat dipertimbangkan sebagai salah satu metode intervensi kelompok guna mengatasi masalah kecemasan pada remaja.